A Multi-Agent Activity-Based Model of Facility Location Choice and Use. - Arentze, Theo A.; Timmermans, Harry (TH Zürich, NSL, 2007)
Die Autoren des Beitrags haben langjährige, auch praktische Erfahrungen mit dem System ALBATROSS, das im Rahmen der Verkehrsvorhersage menschliche Tagesabläufe im statischen urbanen System simuliert, Sie wenden sich nun der dynamischen Entwicklung dieses Systems zu, insbesondere den Landnutzungs-Entscheidungen sowohl der Bewohner als auch der kommerziellen Akteure. Der Beitrag beschreibt die konzeptionellen Überlegungen, um ein solches Simulations-System mit ALBATROSS zu verbinden, eine erste Implementation, sowie deren Anwendung auf ein illustratives Beispiel. difu

Recent years have seen the development of several operational activity-based models of travel demand. Although the advantage of the activity-based approach over trip-based and tour-based approaches has been demonstrated, applications in integrated land-use transport models have not yet been realized. The paper proposes a model system that intends to fill this gap. The model represents individuals and firms/planners as agents in a multi-agent system. An existing activity-scheduling model, ALBATROSS, and a new model of facility location choice are included as methods of the demand and supply side agents respectively. Simulation results illustrate the increase in behavioral complexity that can be achieved with this approach. difu
Keywords: Stadtplanung; Planung; Planungsinstrument; Simulation; Modell; Standort; Standortwahl; Standortplanung; Verkehrsprognose; Mobilität; Verhalten; Standortentscheidung; Modellsimulation; Simulationssystem; Verkehrsstrom; Alltagsmobilität; Fallstudie